2018
DOI: 10.1515/ract-2018-2957
|View full text |Cite
|
Sign up to set email alerts
|

Study of the redistribution of U, Zr, Nb, Tc, Mo, Ru, Fe, Cr, and Ni between oxide and metallic phases in the matrix of a multiphase Chernobyl hot-particle extracted from a soil sample of the Western Plume

Abstract: Abstract A “hot particle” found 6 km west of the Chernobyl nuclear power plant 4 years after the Chernobyl severe nuclear accident was analysed by scanning electron microscopy and electron probe micro-analysis. The matrix of the particle consists of relics of partly molten UO2 nuclear fuel and two different phases of solidified U–Zr–O melt (U0.77Zr0.23O2 and U0.67Zr Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Accidental (like Chernobyl and Fukushima) and routine releases of radionuclides into the environment result in the formation of U oxide NPs. [29][30][31][32] It has also been shown that the dissolution of spent nuclear fuel may result in the formation of UO 2 NPs that should be taken into account in the performance assessment of repositories, 33 considering that conditions in deep geological repositories are expected to be reducing.…”
Section: Introductionmentioning
confidence: 99%
“…Accidental (like Chernobyl and Fukushima) and routine releases of radionuclides into the environment result in the formation of U oxide NPs. [29][30][31][32] It has also been shown that the dissolution of spent nuclear fuel may result in the formation of UO 2 NPs that should be taken into account in the performance assessment of repositories, 33 considering that conditions in deep geological repositories are expected to be reducing.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of "hot" particles with a non-oxidized matrix of U-bearing metallic Zr (Pöml and Burakov, 2017) and the presence of partly molten nuclear fuel (Pöml and Burakov, 2018) confirmed that local UO 2 -Zr interaction occurred at a very high temperature (>2,850 °C) and probably lasted a few microseconds or less. The presence of Zr-U-Fe-O suggested the melting of the spacer grids and was a clue to the relocation of corium melt with fuel, cladding, and steel components (Shiryaev et al, 2018).…”
Section: Chernobyl Npp Unit 4 Accidentmentioning
confidence: 87%
“…An overview of recent studies (Shiryaev et al, 2016;Pöml and Burakov, 2017;Zubekhina and Burakov, 2017;Pöml and Burakov, 2018;Shiryaev et al, 2018;Zubekhina et al, 2019;Shiryaev et al, 2020;Zubekhina et al, 2021;Shiryaev et al, 2022;Lönartz et al, 2023) shows that, even after more than 30 years of investigation, Chernobyl sample analysis could contribute additional information about accident progression, conditions of corium and "lava" formation, and the processes of their chemical alteration due to aging. Since the damaged fuel was not removed from the destroyed reactor unit, evaluation of the usefulness of sample analysis results for the fuel debris removal process is not possible.…”
Section: Chernobyl Npp Unit 4 Accidentmentioning
confidence: 99%
“…In the case of accidental fuel fallout, such as the Chernobyl fallout, uranium enters the environment initially as U(IV) species, mainly as uranium dioxide, which is partially oxidized, and sometimes as mixed uranium-zirconium dioxide (UO 2+x , (U, Zr)O 2 ) (Pöml and Burakov, 2018 ; Shiryaev et al, 2018 ) ( Figure 1 ). The solubility of these fuel particles depends more on the conditions of their formation than on the environment (Kashparov et al, 2019 ).…”
Section: Uraniummentioning
confidence: 99%